The Role of Picture Media in Enhancing Children's Learning Interest Through the Implementation of Religious and Moral Values in Group B of Aisyiyah 1 Kindergarten, Palu - Rani Rahmaniah; Nurhayati; Mohammad Akbar; Andi Agusniatih (Universitas Al-Hikmah Indonesia, 2026)
This study aims to examine the role of visual media in increasing children's interest in learning through the application of religious and moral values ​​in Group B of Aisyiyah 1 Kindergarten, Palu. The focus of this study includes the introduction of the hijaiyah letters, images of the Kaaba, and images of houses of worship. Visual media is considered an effective visual media in early childhood learning because it can attract attention, foster curiosity, and help children understand abstract concepts more realistically. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of 15 children, namely 8 boys and 7 girls. Data were collected through observation, interviews, and documentation techniques, then analyzed using percentage techniques. The results showed that in the aspect of recognizing the hijaiyah letters, most children were in the Very Well Developing (BSB) and Developing According to Expectations (BSH) categories. Similar findings were also seen in the introduction of images of the Kaaba and houses of worship, where most children showed good development. However, there were still several children in the Starting to Develop (MB) and Not Yet Developing (BB) categories. Therefore, it can be concluded that the use of visual media has a significant role in increasing children's interest in learning through the application of religious and moral values.